Avaliação dos diferentes graus de fibrose na esteatohepatite não- alcoólica por métodos semiquantitativos, quantitativo, elastográfico e escores preditores de fibrose não invasivos - Túlio de Paula Vasconcelos (2023)
Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease in the world, although knowledge about its pathophysiology remains insufficient. Similarly, good markers of disease severity and evolution are not recognized, with the degree of liver fibrosis being the only validated prognostic factor. In order to assess the degree of liver fibrosis, an invasive method can be used, in this case biopsy, which is considered the gold standard; and non-invasive methods such as clinical scores and liver stiffness assessment methods using ultrasound or magnetic resonance imaging. Therefore, the present project aimed to evaluate the degree of hepatic fibrosis by means of semi-quantitative (histological scores) and quantitative (morphometry) methods in liver biopsies of patients diagnosed with non- alcoholic steatohepatitis (NASH) and to compare with the elastographic values of hepatic stiffness and clinical scores predictors of fibrosis (FIB-4, APRI score and AST/ALT ratio) of the same patients. A total of 451 patients undergoing clinical follow-up at the Non-Alcoholic Fatty Liver Disease Outpatient Clinic at HC/UFMG were selected. Twenty-one patients met the inclusion criteria in the study, 20 women and one man. In addition to these, three more HPMMG patients were included, in the routine of a gastroenterology office, with two women and one man, all meeting the same inclusion criteria. The mean age was approximately 60 years and the median interval between biopsy and elastography was 8.5 months. According to the Laennec score, 15 patients were cirrhotic (five in each degree) and nine were non- cirrhotic. Significant differences were observed between the groups with and without cirrhosis regarding FIB-4 scores, APRI and morphometry, but not found regarding transient elastography and AST/ALT ratio. Laennec's histological score showed a direct correlation with transient elastography, clinical FIB-4 score and morphometry. However, when separated by grades (4A, 4B and 4C), cirrhotic patients, according to Laennec, presented a correlation only with morphometry. A ROC curve analysis was performed in order to assess the sensitivity and specificity of the cutoff point that best discriminates a patient with cirrhosis based on the Laennec score for the variables FIB-4 (1.070), APRI (0.450) and morphometry (13.2550). For transient elastography and AST/ALT ratio, the areas under the curves (AUROC) found were not statistically significant. Clinical FIB- 4, APRI scores and morphometry were good predictors of the degree of liver fibrosis. There was a correlation between the Laennec score and ET, FIB-4 and morphometry. The sample size impaired the statistical evaluation.